Recent developments in topical wound therapy: impact of antimicrobiological changes and rebalancing the wound milieu - Renner, Regina; Erfurt-Berge, Cornelia (BioMed Research International, 2014)
Wound therapy improves every year by developing new wound treatment options or by advancing already existing wound materials, for example, adding self-releasing analgesic drugs or growth factors to wound dressings, or by binding and inactivating excessive proteases. Also new dressing materials based on silk fibers and enhanced methods to reduce bacterial burden, for example, cold argon plasma, might help to fasten wound healing.
EVALuna2:19478